Aktivitas Isolat Actinomycetes dari Rumput Laut (Eucheuma cottonii) sebagai Penghasil Antibiotik terhadap Staphylococcus aureus dan Escherichia coli - NANIK SULISTYANI; ACHMAD NURYADIN AKBAR (JURNAL ILMU KEFARMASIAN INDONESIA, 2014)
Actinomycetes are microbial group of the most widely produced bioactive compound as antibiotics.This study was intended to isolate Actinomycetes from seaweed Eucheuma cottonii and to identify the activity of isolated Actinomycetes as antibiotic producer against Staphylococcus aureus and Escherichia coli. Furthermore, the research was aimed to know the spots on thin-layer chromatography(TLC) which has antibacterial activity against S. aureus and E. coli. Isolation of Actinomycetes from E. cottonii was carried out with a spread plate method. The activity test of Actinomycetes as antibiotic producer against S. aureus and E. coli was performed by cup plate method. TLC bioautography was done with stationary phaseof silica gel GF254 and mobile phase of n-hexane : ethylacetate (2:3). The results showed that RL 6 and RL 12 isolate produced antibiotic against S. aureus and E. coli.The TLC bioautography result of ethyl acetate extracts of RL 6 and RL 12 cultures against S. aureus and E. coli showed a inhibition zone at Rf 0.05 and 0.22, respectively.